Răspunsuri

2014-10-26T18:43:50+02:00
S1=(9-13-5)/2+2=(-4-5)/2+2=-9/2+2=(-9+4)/2=-5/2
S2=176/100-204/100+112/100+92/100+323/100=(176-204+112+92-323)/100=
=(-28+112+92-323)/100=(84+92-323)/100=(176-323)/100=-147/100=-1,47
S3=-113/20+1225/100-71/10+565/100-179/10 aducem la acelasi numitor=
(-113·5+1225-71·10+565-179·10)/100=(-565+1225-710+565-1790)/100=
=(660-710+565-1790)/100=(-45+565-1790)/100=(520-1790)/100=
=-1270/100=-12,7
2014-10-26T18:49:42+02:00
S1= (9-13-5)/2 + 4/2= - 5/2

S3=113/20 -71/10 +(12,25+5,65) - 17,9
S3=113/20 - 142/20= - 129/20

S2= 1,76+1,12+0,92 - (2,04+3,23) = 3,8 - 5,27 = -1 ,47

nu e bine
scz
scrisesem gresit la S2 dar am corectat